Combined effects of fibrinogen genetic variability on atherosclerosis in patients with or without stable angina pectoris: Focus on the coagulation cascade and endothelial function - Papageorgiou, N; Tousoulis, D; Miliou, A; Hatzis, G; Kozanitou, M; Androulakis, E; Charakida, M; Antonopoulos, A; Antoniades, C; Briasoulis, A; Giolis, A; Bouras, G; et al. (2013)
Background Fibrinogen is a coagulation/inflammatory biomarker strongly associated with atherogenesis. Data have reported that the genetic variability on fibrinogen chains may affect the atherosclerotic process and the risk of coronary artery disease (CAD). We examined the combined effects of the G455A and the G58A fibrinogen genetic polymorphisms on prothrombotic profile, endothelial function and the risk of CAD in a Caucasian population. Methods We recruited 422 patients with angiographically documented CAD and 277 controls matched for age and gender. The two polymorphisms were genotyped by polymerase chain reaction and restriction endonuclease digestion. Fibrinogen and D-Dimers levels, as well as factors' (f) V, X activity were measured by standard coagulometry techniques. Endothelial function was assessed by the flow mediated dilatation (FMD) of the brachial artery. Results The two polymorphisms had no significant effect on the risk for CAD. Although the 58AA subjects had not significantly different levels of fibrinogen compared with the 58GG + GA in both groups (p = NS), we importantly found that the 455AA homozygosity was associated with increased fibrinogen levels not only in the control group (p = 0.035), but also in the CAD group (p < 0.001) compared to the G allele carriers. Moreover, both the 58AA (p = 0.016) and 455AA homozygotes (p = 0.022) presented with higher levels of D-Dimers in the CAD group. Interestingly, the 455AA homozygotes had increased fV activity in the CAD group (p = 0.048). However, no significant effects were observed on fX activity and FMD. Conclusions Both fibrinogen polymorphisms are capable to modify the atherosclerotic process via their effects on the coagulation cascade. © 2013 Elsevier Ireland Ltd.